Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Indeks Pembangunan Manusia Kabupaten/Kota NTB Tahun 2018-2022 - M. Hafizal Insani; Abdul Manan; Eka Agustiani (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research aims to determine the influence of local original income (regional taxes and regional levies), and balancing funds (profit sharing funds, general allocation funds, and special allocation funds), on the Regency/City Human Development Index in NTB Province for 2018-2022. Data analysis uses panel data regression with the fixed effect model method. The results of this research show that: (1) Regional taxes do not have a significant effect on the Regency/City Human Development Index in NTB Province. (2) Regional levies do not have a significant effect on the Regency/City Human Development Index in NTB Province. (3) Profit Sharing Funds do not have a significant effect on the District/City Human Development Index in NTB Province. (4) General Allocation Funds do not have a significant effect on the Regency/City Human Development Index in NTB Province. (5) Special Allocation Funds have a positive and significant effect on the District/City Human Development Index in NTB Province. Keywords: Original Regional Income, Balancing Funds, Human Development Index, NTB Province.